Selinunt, Italien. Die Arbeiten der Jahre 2017 und 2018 - Bücherl, Heike; Dally, Ortwin; Helas, Sophie; Schön, Frerich (e-Forschungsberichte des DAI, 2019)
The excavation report on the research activities in Selinunte in 2017 and 2018 contains reports on new excavations in the northeastern section of the Agora, where a burial site of the first generation of settlers had been transformed during the Archaic period into a sacred space remembering the predecessors, a new project aiming the investigation of the 5th century BC temples A and O on the acropolis and their transformation until the early medieval ages and new natural science based studies. They took place on the acropolis as well and have been analyzing the plasterwork of cisterns of some buildings of the Punic period (mid 4th–mid 3rd centuries BC).